Esophageal Cancer-Related Gene-4 Contributes to Lipopolysaccharide-Induced Ion Channel Dysfunction in hiPSC-Derived Cardiomyocytes - Xu Q; Zhang X; Hao M; Dang X; Xu Q; Cyganek L; Akin I; Tang D; Liao B; Zhou X; Lan H (Journal of Inflammation Research)
Qiang Xu,1,2,* Xiangjie Zhang,3,* Maolin Hao,3,* Xitong Dang,3 QianQian Xu,3 Lukas Cyganek,4,5 Ibrahim Akin,2,6 Dan Tang,7 Bin Liao,8 Xiaobo Zhou,2,3,6 Huan Lan3 1School of Basic Medical Science, Southwest Medical University, Luzhou, People’s Republic of China; 2First Department of Medicine, Faculty of Medicine, University Medical Centre Mannheim (UMM), University of Heidelberg, Mannheim, Germany; 3Key Laboratory of Medical Electrophysiology, Ministry of Education & Medical Electrophysiological Key Laboratory of Sichuan Province, Institute of Cardiovascular Research, Department of Cardiology, The Affiliated Hospital, Southwest Medical University, Luzhou, People’s Republic of China; 4Stem Cell Unit, Clinic for Cardiology and Pneumology, University Medical Center Göttingen, Göttingen, Germany; 5DZHK (German Center for Cardiovascular Research), Partner Site, Göttingen, Germany; 6DZHK (German Center for Cardiovascular Research), Partner Site, Heidelberg, Mannheim, Germany; 7The First People’s Hospital of Longquanyi District, Chengdu/West China Longquan Hospital, Sichuan University, Chengdu, People’s Republic of China; 8Department of Cardiac Macrovascular Surgery, Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huan Lan, Key Laboratory of Medical Electrophysiology, Ministry of Education & Medical Electrophysiological Key Laboratory of Sichuan Province, Institute of Cardiovascular Research, No. 1 section 1 of Xiang Lin Road, Longmatan District, Luzhou City, Sichuan, People’s Republic of China, Tel +0086-0830-3160619, Email lanhuan@swmu.edu.cn Xiaobo Zhou, First Department of Medicine, Faculty of Medicine, University Medical Centre Mannheim (UMM), University of Heidelberg, Theodor-Kutzer-Ufer 1-3, Mannheim, Baden-Württemberg, Germany, Tel +0049-621-3831448, Email Xiaobo.zhou@medma.uni-heidelberg.deBackground and Purpose: Esophageal cancer-related gene-4 (ECRG4) participate in inflammation process and can interact with the innate immunity complex TLR4-MD2-CD14 on human granulocytes. In addition, ECRG4 participate in modulation of ion channel function and electrical activity of cardiomyocytes. However, the exact mechanism is unknown. This study aimed to test our hypothesis that ECRG4 contributes to inflammation-induced ion channel dysfunctions in cardiomyocytes.Methods: Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) generated from three donors were treated with lipopolysaccharide (LPS) to establish an endotoxin-induced inflammatory model. Immunostaining, real-time PCR, and patch-clamp techniques were used for the study.Results: ECRG4 was detected in hiPSC-CMs at different differentiation time. LPS treatment increased ECRG4 expression in hiPSC-CMs. Knockdown of ECRG4 decreased the expression level of Toll-Like-Receptor 4 (TLR4, a LPS receptor) and its associated genes and inflammatory cytokines. Furthermore, ECRG4 knockdown shortened the action potential duration (APD) and intercepted LPS-induced APD prolongation by enhancing ISK (small conductance calcium-activated K channel current) and attenuating INCX (Na/Ca exchanger current). Overexpression of ECRG4 mimicked LPS effects on ISK and INCX, which could be prevented by NFκB signaling blockers.Conclusion: This study demonstrated that LPS effects on cardiac ion channel function were mediated by the upregulation of ECRG4, which affects NFκB signaling. Our findings support the roles of ECRG4 in inflammatory responses and the ion channel dysfunctions induced by LPS challenge.Keywords: esophageal cancer-related gene-4, arrhythmias, lipopolysaccharide, human-induced pluripotent stem cell-derived cardiomyocytes, inflammation